ENT 530 Social Media Portfolio: Nurbella Empire / Hanis Mohd Noor - Mohd Noor, Hanis (2020)
Nurbella Empires Sdn Bhd was founded in 2018 and keeps growing company today by using innovative concepts for new product creation to satisfy all muslimah needs. It is also known as one of the fashion muslimah platform that produces muslimah attire with top 1 brand in Malaysia. The main objective of the business is to provide the best quality, exclusive and trendy attire to all muslimah in keeping with the passage of time. In addition, Nurbella Empires is a company that produce and creating with their own of handsock which consist of variety types and colours. Handsock is the main product of Nurbella Empires. The target customers is to woman in the age of 12- 60 years. It offers affordable and cheaper price of handsocks with exclusive made in the market. This is because, not everyone afford to buy and wear hansocks to covers the ‘aurat’. Thus, I used online platform in order to promote, marketing and sales of handsocks product by Nurbella. I also learned to use ecommerce platform in doing the business or to record the sales. The management of Nurbella handsocks consists of Mrs. Nur Izati Ghani. I create Facebook page in order to expand the business well through social media. Copywriting techniques are important for every business in order to convince and influence prospects online to buy the products. Teaser, hardsell, softsell and also frequency post are use for interest advertising way to grabs customers attention and to make the product which is handsock by Nurbella easy to known from many people. From the FB page, I able to gets 119 likes and 120 followers. The customers can visit my facebook page to know more for the details about Nurbella handsocks. This helped the company to save a lot of cost involved and can reach the widen target market. Besides, most customers of Nurbella handsock give a positive feedback about it which in turns makes them to repeat buying that handsocks again. This will make the Nurbella handsocks become well known from many customers. Nurbella handsocks also have plans to expand their business to global market and reach the Asian country to enhance the brand recognition and increase the sales well. It also aimed to fulfill customer’s requirement to reach the fully satisfaction from many customers.